For the record: Practicing critical software literacy in writing centers - Bryan, Matthew (Computers and composition, 2024)
•“Big data” methods highlight the need for analyses of writing center software.•TutorTrac advances a rhetoric of recordkeeping that refashions center practices.•Writing centers are ideal spaces for the development of critical software literacy. While “big data” approaches to writing center research represent promising angles from which to understand the intellectual labor happening during tutorials, aggregation strips away the context in which writing center texts and data are originally constructed. In fact, new methods such as the large-scale corpus analysis of writing center session notes highlight the need for more critical analyses of the administrative software used to generate, archive, and distribute these texts. Drawing on Bogost's (2007) conception of procedural rhetoric and Manovich's (2013) understanding of softwarization, this article seeks to address this gap by recontextualizing writing center session notes within the layered arguments constructed by TutorTrac, a scheduling platform used by many centers. I argue this software advances a rhetoric of recordkeeping that, left unrecognized, risks shifting center practices away from stated commitments and values. In demonstrating how writing center practitioners can employ an understanding of procedural rhetoric to interrogate such applications, this study suggests more attention be dedicated to critical readings of software in writing centers.